Communication and materiality: written and unwritten communication in pre-modern societies - Enderwitz, Susanne; Sauer, Rebecca (Materiale Textkulturen, 2015)
This volume reconsiders literacy and communication in pre-modern societies, focusing especially on how material form affects the way textual artefacts are understood and interpreted. By bringing together scholars from diverse disciplines such as archaeology, medieval studies, and Islamic studies, this volume provides the specialist and non-specialist with insights on how humans express themselves through writing and material culture.
5 schw.-w. u. 18 farb. Abb
open access
Keywords: Geschichte 3000 v. Chr.-1500; Schriftliche Kommunikation